2018
DOI: 10.14744/eej.2018.18291
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting the Outcome of Non-Surgical Endodontic Treatments Performed by Undergraduate Students in a Greek Dental School

Abstract: To evaluate the outcome of initial endodontic treatments performed by undergraduate students in a Greek dental school and to determine the factors that may impact the treatment outcome. Methods: From a randomly selected sample of 677 non-surgical endodontic treatments performed between 2012 and 2015, follow-up appointments were scheduled with patients whose dental records matched the inclusion criteria. After clinical and radiographic examination, the treatment outcome was classified as 'success' (healed/heali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…Even though the current study showed statistically insignificant correlation between technical quality and endodontic outcome, the apical extension of root canal fillings within 2 mm from the radiographic apex was found associated with the highest success rate of endodontic outcome (67.5%), which is consistent with other studies [21,25,27,[34][35][36]. The present study also reported highest failure rates in unacceptable apical extension of obturation (40%) as compared to presence of void (21.4%) and endodontic mishaps (24.1%).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Even though the current study showed statistically insignificant correlation between technical quality and endodontic outcome, the apical extension of root canal fillings within 2 mm from the radiographic apex was found associated with the highest success rate of endodontic outcome (67.5%), which is consistent with other studies [21,25,27,[34][35][36]. The present study also reported highest failure rates in unacceptable apical extension of obturation (40%) as compared to presence of void (21.4%) and endodontic mishaps (24.1%).…”
Section: Discussionsupporting
confidence: 91%
“…Dental undergraduates in the current study achieved an endodontic success rate of 66.7% after an average of 2.8 years follow-up, which was lower as compared to the dental undergraduates in other countries [20][21][22][23] and similar to Ng et al [19]. In UK, Heling and Tamshe [20] reported an overall success rate of 70% in 213 teeth that were treated by dental undergraduates.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations